(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to explore the impact of performance management methods on enhancing productivity at King Fahd Specialist Hospital in Buraidah. The study was conducted on a sample of 390 employees. The researcher used a descriptive analytical approach, relying on a questionnaire to collect data. The data were analyzed using SPSS- Version 24, focusing on frequency distribution and employing the Chi-square statistical test to measure the significance level of the responses. The results highlighted the importance of performance management methods in improving productivity and work quality, revealing that these methods positively influence job discipline and motivate employee innovation. The study also affirmed the role of effective communication and feedback in achieving better performance. The study concludes with a recommendation for the continuous development and improvement of performance management methods at the hospital to attain the highest levels of productivity and efficiency. This includes focusing on innovation and feedback as essential aspects of enhancing performance and job satisfaction.